Quality Of Life among Pregnant Women in a Tertiary Care Hospital - K.C, Mamta; K.C, Nyamika; Tripathi, Pratikshya; Katuwal, Kumari; Karki, Pratiksha; Pokhrel , Bishika (Journal of Nobel Medical College, 2025)
Background: Pregnancy brings hormonal, metabolic, and emotional changes that can significantly influence a woman’s quality of life. This study aimed to assess Quality of life among pregnant women.Materials and Methods: A descriptive cross-sectional study was conducted at the ANC OPD of Nobel Medical College Teaching Hospital, Biratnagar, from November 2024 to March 2025. A total of 184 pregnant women were selected through convenience sampling. Data were collected via face-to-face interviews using the RAND SF-36 questionnaire. Descriptive statistics (frequency, percentage, median, interquartile range) and inferential statistics (Mann-Whitney U test) were used for analysis.Results: The median QoL score was 67 (IQR: 62–74), with scores of 60 (51–67) for the physical component and 75 (70–82) for the mental component. The highest domain score was in emotional role limitation 100 (66.7–100), while the lowest was in physical role limitation 25 (0–50). Significant differences were noted in the Emotional Role Limitation domain based on the age group (p=0.006) and educational status (p=0.043). Similarly, general Health domain demonstrated a significant difference in terms of religious groups (p=0.024). Likewise, significant differences were observed between occupation in the domain of Energy/Fatigue (p=0.015), Emotional Wellbeing (p=0.002), and General Health (p=0.003). Also, significant difference in pain domain was found between nulliparous and parous women.Conclusion: Based on the findings of the study, it can be concluded that mental health component scored higher than the physical health component. Among all domains, the highest score was observed in emotional role limitation while the lowest was in physical role limitation.